2021
DOI: 10.1371/journal.pone.0252569
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for carotid and femoral artery intima-media thickness in a non-diabetic sleep clinic cohort

Abstract: Introduction The impact of sleep disordered breathing (SDB) on arterial intima-media thickness (IMT), a surrogate measure for cardiovascular disease, remains uncertain, in part because of the potential for non-SDB vascular risk factor interactions. In the present study, we determined predictors for common carotid (CCA) and femoral (CFA) artery IMT in an adult, sleep clinic cohort where non-SDB vascular risk factors (particularly diabetes) were eliminated or controlled. Methods We recruited 296 participants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Participants in this present report also underwent carotid and femoral artery ultrasonography for measurement of intima media thickness. These results have been reported previously [ 14 ].…”
Section: Methodssupporting
confidence: 92%
“…Participants in this present report also underwent carotid and femoral artery ultrasonography for measurement of intima media thickness. These results have been reported previously [ 14 ].…”
Section: Methodssupporting
confidence: 92%
“…Kozàkovà et al found that SB was related to worsened CCA but not internal carotid artery IMT, while all intensities of PA, particularly VPA, were associated with lower CCA IMT 70. Five other studies showed that increased time spent in PA, of non-specific or light intensity, was related to reduced risk of carotid artery atherosclerosis 26 27 34 71 72. Parsons et al found an association between increased SB and worse cIMT, while an inverse relationship was found between LPA and MVPA with cIMT, although MVPA did not have a stronger association than LPA 65.…”
Section: Resultsmentioning
confidence: 99%